Acute Liver Failure in a Neonate; A Case Report - Fakih, Misbah; Tariq, Sidrah; Shoaib, Muhammad; Ikram, Farooq; Asad, Hafsa (Pakistan Armed Forces Medical Journal, 2024)
Neonatal hemochromatosis is a rare disorder that poses significant mortality and morbidity risks. It is one of the causes of acute liver failure in neonates. We report a case of a 15-day-old girl with complaints of jaundice and progressive liver failure; a family history of 3 early neonatal deaths with similar complaints led to the strong suspicion of Gestational Alloimmune Liver Disease. Clinicians should consider Gestational Alloimmune Liver Disease in cases of fetal demise, stillbirth, and neonatal acute liver failure, as treatment is available and effective for subsequent pregnancies.